Hyperpolarized MRI with silicon micro and nanoparticles: Principles and applications. (13th May 2021) - Pudakalakatti, Shivanand; Enriquez, José S.; McCowan, Caitlin; Ramezani, Saleh; Davis, Jennifer S.; Zacharias, Niki M.; Bourgeois, Dontrey; Constantinou, Pamela E.; Harrington, Daniel A.; Carson, Daniel; Farach‐Carson, Mary C.; Bhattacharya, Pratip K.
Abstract: Silicon‐based micro and nanoparticles are ideally suited for use as biomedical imaging agents because of their biocompatibility, biodegradability, and simple surface chemistry that facilitates drug loading and targeting. A method to hyperpolarize silicon particles using dynamic nuclear polarization (DNP), which increases magnetic resonance (MR) imaging signals by several orders‐of‐magnitude through enhanced nuclear spin alignment, was developed to allow silicon particles to function as contrast agents for in vivo magnetic resonance imaging. In this review, we describe the application of the DNP technique to silicon particles and nanoparticles for background‐free real‐time molecular MR imaging. This review provides a summary of the state‐of‐the‐science in silicon particle hyperpolarization with a detailed protocol for hyperpolarizing silicon particles. This information will foster awareness and spur interest in this emerging area of nanoimaging and provide a path to new developments and discoveries to further advance the field. This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Therapeutic Approaches and Drug Discovery > Emerging Technologies Abstract : Hyperpolarized silicon MRI as a platform imaging technology for nanomedicine.